Fluoroarene Complexes with Small Bite Angle Bisphosphines: Routes to Amine–Borane and Aminoborylene Complexes. Issue 38 (4th August 2017) - Colebatch, Annie L.; McKay, Alasdair I.; Beattie, Nicholas A.; Macgregor, Stuart A.; Weller, Andrew S.
Abstract : Fluoroarene complexes of the small bite angle bisphosphine Cy2 PCH2 PCy2 (dcpm) have been prepared: [Rh(dcpm)(η 6 ‐1, 2‐F2 C6 H4 )][Al{OC(CF3 )3 }4 ] and [Rh(dcpm)(η 6 ‐1, 2, 3‐F3 C6 H3 )][Al{OC(CF3 )3 }4 ]. These complexes act as precursors to a previously inaccessible σ‐amine–borane complex [Rh(dcpm)(η 2 ‐H3 B· NMe3 )][Al{OC(CF3 )3 }4 ] of a small bite‐angle phosphine. This complex is a poor catalyst for the dehydrocoupling of H3 B· NMe2 H. Instead, formation of the bridging borylene complex [{RhH(µ‐dcpm)}2 (µ‐H)(µ‐BNMe2 )][Al{OC(CF3 )3 }4 ] occurs, which has been studied by NMR, mass spectrometry, crystallographic and DFT techniques. This represents a new route to bridging borylene complexes. Abstract : Synthesis of a Rh–trifluoroarene complex allows access to a bridging borylene complex by an amine–borane dehydrogenation/B–H activation.